Hubungan Antara Karakteristik Ibu Dan Pengetahuan Terhadap Imunisasi Dasar Lengkap Pada Bayi Di Klinik Sehati Tahun 2024 - Saragih, Pebrinawanti; -, Ruseni (Jurnal Maternitas Kebidanan, 2024)
The World Health Organization (WHO) states that an estimated 6 million children did not receive vaccinations in 2019, and an estimated 25 million children did not receive vaccinations in 2020. Immunization in 2021 prevented 3.5–5 million deaths from diseases such as diphtheria, tetanus, pertussis, influenza, and measles (WHO 2021). The purpose of this study is to determine the relationship between maternal characteristics and knowledge regarding complete basic immunization in infants at the Sehati Clinic. This research is descriptive in nature and uses primary data. The population consists of mothers who bring their babies to receive basic immunization, totaling 20 individuals. The sample was selected using the time sampling method. Data analysis was conducted using univariate, bivariate, and multivariate analyses. Bivariate analysis revealed a significant relationship between age, education, parity, and knowledge with immunization completeness, as determined by the Chi-Square statistical test with a p-value < 0.05. However, there was no significant relationship between maternal occupation and immunization completeness, as the Chi-Square test did not yield a p-value < 0.05. The conclusion from the bivariate analysis is that there is a significant relationship between age, education, parity, and knowledge with immunization completeness, while there is no significant relationship between maternal occupation and immunization completeness. It is recommended that mothers enhance their knowledge about the importance of providing complete basic immunization to their babies through reading books, attending counseling sessions, and consulting with healthcare professionals. Keywords: Characteristics, Knowledge, Immunization Completeness